i really need help with some factoring!!
ive been working on these 2 problems foreverrr!!!!!!!!!!
(x+a)^2 - 2(x+a) (y+a) + (y+a)^2
and
x^2-8x(x-3y) +16(x-3y)^2
Hi xosherry,
For the first problem,
$\displaystyle (x+a)^2 -2(x-a)(y+a) +(y+a)^2$
try a change of variables to maybe simplify things
let $\displaystyle u=(x+a) \; v=(y+a)$ then rewriting the equation results in
$\displaystyle u^2-2uv+v^2 \ { } = \ { } (u-v)(u-v)=(u-v)^2$
now replacing what we defined as u and v we get
$\displaystyle [ (x+a)-(y+a)]^2 \;=[x+a-y-a]^2 =(x-y)^2$
For the second problem $\displaystyle x^2 -8x(x-3y) +16(x-3y)^2$
using the same technique let $\displaystyle u=x \; v=(x-3y)$
rewriting the equation will result in
$\displaystyle u^2 -8uv-16v^2 $
factor this expression and back substitute for u and v
Hope this helps